Integrating BDI agents with agent-based simulation platforms - Singh, Dhirendra; Padgham, Lin; Logan, Brian (2017)
This paper describes an integration framework that allows development of simulations where the cognitive reasoning and decision making is programmed and executed within an existing BDI (Belief, Desire, Intention) system, and the simulation is played out in an existing ABM (Agent Based Modelling) system. The framework has a generic layer which manages communication and synchronisation, a system layer which integrates specific BDI and ABM systems, and the application layer which contains the program code for a particular application. The code is available on GitHub: https://github.com/agentsoz/bdi-abm-integration